Extreme drought-heatwave events threaten the biodiversity and stability of aquatic plankton communities in the Yangtze River ecosystems - Jixuan Lyu; Yong Shi; Tao Liu; Xiaomei Xu; Shengjing Liu; Guang Yang; Dong Peng; Yubing Qu; Shuo Zhang; Chonghao Chen; Yanxu Zhang; Jianhua Gao (Communications Earth & Environment)
Abstract Rivers are crucial to biogeochemical cycles, connecting terrestrial, oceanic, and atmospheric systems. However, their ecosystems are increasingly threatened by extreme weather events. Here we used the environmental DNA approach to assess the impact of extreme drought-heatwave events on the aquatic plankton communities of the Yangtze River. We showed that an extreme drought-heatwave event reduced the α diversity of communities, increased their β diversity, and simultaneously simplified and destabilized community network structure. This event also shifted the dominant algae taxa from Bacillariophyta to Cyanobacteria, accompanied by increases in organic carbon and labile organic carbon contents. Globally, temperature rises during this extreme drought-heatwave event are more pronounced in high-latitude regions, likely amplifying impacts on river ecosystem biodiversity and stability. Our findings highlight the vulnerability of river ecosystems to extreme events and underscore the need to mitigate climate change’s effects on river ecosystems.